COLOR DOPPLER ULTRASONOGRAPHY IN DIAGNOSIS OF BUDD-CHIARI SYNDROME - İlhan ERDEN and Suat AYTAÇ and Ayşe ERDEN and Abdülkadir DÖKMECİ and Kadir BAHAR and Hüseyin SÜMER (Turkish Journal of Gastroenterology, 2020)
-